THE EFFECT OF AUTHENTIC LEADERSHIP ON TURNOVER INTENTION WITH AFFECTIVE COMMITMENT AS A MEDIATION VARIABLE ON EMPLOYEES OF PT. BPR GEMA PESISIR - Yustin, Tria Ginda; Zona, Mega Asri (Human Resource Management Studies, 2023)
Research analyzes the effect of authentic leadership on turnover intention with affective commitment as a mediating variable for PT. BPR Gema Pesisir. This type of research is quantitative research and is a causal research. The population used is all employees at PT. BPR Gema Pesisir, with a total of 53 people. The sampling technique was taken using a total sampling technique where the number of samples is equal to the total population. Collecting data using a questionnaire survey. The analysis technique used is PLS (Partial Least Square), which is a structural equation analysis technique (SEM) using SmartPLS 4 software. The results of data processing in this study indicate that affective commitment mediates authentic leadership on turnover intention . to employees of PT. BPR Gema Pesisir.